Propuesta de un sistema de gestión de compras e inventarios para reducir los costos operativos en la empresa Arcosu Corporation S.A.C. de Trujillo - Cadenillas Paredes, Jesus Ysrael (2023)
The present research work had the general objective of proposing a purchasing and inventory management system to reduce operating costs in the company Arcosu Corporation S.A.C. of Trujillo. To carry out the study, a referential theoretical framework of background and theoretical concepts is established. The unit of analysis was made up of the purchasing and inventory processes of the organization where the problem for the preparation of the proposal was prolonged. For the development of the study, the purchase and inventory process was taken as a sample, where it is limited that the organization has a series of limitations when storing and distributing its product, which is displayed when carrying out work activities. For this reason, the diagnosis of purchasing and inventory management showed proposing a series of tools such as the 5S methodology, ABC method and management improvement so that in this way purchasing and inventory management can be improved and provide a better service. to the clients. Finally, it can be concluded by pointing out that the management of purchases and inventories as a proposal will allow greater control over the products stored inside and reduce the operating costs of the organization's operations.